Konsep Kota Pintar Yang Diterapkan Pada Sistem Gardu Tol Otomatis (Gto) - Damuri, Amat; Anagora, Roni; Hendratna, Gempa; Syah Putra, Arman (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2020)
The background of this research is to develop the existing system of Automatic Toll Gate System(ATGS) because there are still shortcomings of the existing system, by developing this system sothat motorists can pass the Automatic Toll Gate System (ATGS) quickly without having to queueto eliminate congestion. at the Automatic Toll Gate System (ATGS). The research method used inthis research is to conduct a literature study and library study, by using the two methods it will finda research problem that can be used as a topic in the research in this paper, with a lot of researchinto the problem it will make the research more in-depth and can be understood in future research.In this research, it is expected to produce a proposed system that can be developed in assisting thedevelopment of the Automatic Toll Gate System (ATGS) in order to help expedite motorists topass the Automatic Toll Gate System (ATGS), because the current problems often occur atAutomatic Toll Gate System (ATGS) if at a certain time, for example during school holidays and Eid homecoming. In this study the authors used a Radio Frequency Identification (RFID) tool thatwas placed on a vehicle so that sensors could be detected at the Automatic Toll Gate System(ATGS), so the drivers of the vehicle did not have to stop first to pay through the toll lane.